The potential of natural product vs neurodegenerative disorders: In silico study of artoflavanocoumarin as BACE-1 inhibitor. (December 2018) - Razzaghi-Asl, Nima; Karimi, Adibe; Ebadi, Ahmad
Graphical abstract: Highlights: Artoflavanocoumarin possesses essential pharmacophoric groups to inhibit BACE1. Pseudo-axial and equatorial conformations could freely interconvert. The maximum affinity of Artoflavanocoumarin was to Asp32p-Asp228i protonation state. Abstract: Increasing evidence suggests the beneficial impact of flavonoid-rich nutrition on normal cognitive function. It has been revealed that flavonoids can slow neurodegenerative processes in situations such as Alzheimer's disease (AD). The β-secretase (BACE-1) is one of the most studied targets in AD therapy owing to its role in producing Aβ plaques. In fact the unique role of BACE-1 in pathogenesis of neurodegenerative diseases has made it a druggable target to develop anti-AD agents. Taking into account the anti-amyloidogenic and anti-oxidative properties, flavonoids have received considerable attention as lead candidates for anti-AD drug discovery projects. In continuation to our interest toward rational exploration of potential anti-AD agents, it was attempted to conduct a combined structure based in silico study and explore pharmacophore of a flavanocoumarin derivative as BACE-1 Inhibitor. Ab initio studies showed that both pseudo-axial and pseudo-equatorial conformers could convert to each other freely at room temperature. Within this study it was revealed that artoflavanocoumarin possess essential pharmacophoric groups to inhibit BACE-1. Considering four different protonation states of BACE-1 as di-deprotonated, diprotonated, protonated Asp32 and protonated Asp228, it was also found that affinity of artoflavanocoumarin toward different protonation states of BACE-1could be ranked as Asp32p-Asp228i > di-deprotonated ∼ Asp32i-Asp228p >> diprotonated. PMF study on artoflavanocoumarin showed that it could pass 1.8 kcal/mol free energy barrier from water to DPPC lipid bilayer. Moreover the pros and cons of artoflavanocoumarin as a lead compound were elucidated.